Assessment of protein changes in farmed giant catfish (Pangasianodon gigas) muscles during refrigerated storage - Rawdkuen,S. (Wiley-Blackwell, 2015)
Farmed giant catfish (Pangasianodon gigas) muscles (dorsal and ventral sites) were stored in a refrigerator (at 4°C) for 14 days to determine the effect of refrigerated storage on biochemical and physical changes. The analyses were carried out at 0, 2, 4, 7, 10 and 14 days of storage. At day 14, Ca2+-ATPase activity markedly decreased when compared to its value at day 1 (>90%), while a small decrease was observed for surface hydrophobicity and reactive sulfhydryls content. Total volatile basic nitrogen and trichloroacetic-soluble peptide content gradually increased when the storage period was extended. The myosin heavy chain decreased slightly on SDS-PAGE for both meat cuts with increased storage time. Expressible drip and cooking loss were highest during the first day of storage and slightly decreased with storage time. Instrumental hardness was significantly higher in the ventral compared to the dorsal muscle, while the toughness was the highest at the second day of storage. The muscle bundles with scanning electron microscopy were less attached, resulting in the observed big gaps over increasing storage time. Results indicated that changes of proteins have detrimental effects on the quality attributes of farmed giant catfish muscles during refrigerated storage, particularly physical and biochemical properties. © 2010 The Authors. Journal compilation © 2010 Institute of Food Science and Technology.